The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ma14227045
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Heavy Metal Ions from One- and Two-Component Solutions via Adsorption on N-Doped Activated Carbon

Abstract: This paper deals with the adsorption of heavy metal ions (Cu2+ and Zn2+) on the carbonaceous materials obtained by chemical activation and ammoxidation of Polish brown coal. The effects of phase contact time, initial metal ion concentration, solution pH, and temperature, as well as the presence of competitive ions in solution, on the adsorption capacity of activated carbons were examined. It has been shown that the sample modified by introduction of nitrogen functional groups into carbon structure exhibits a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…It can be the result of different metal species presented in the solution within the acidic range of pH values and their different size. In the solutions of pH lower than 6, the dominant species of copper are Cu 2+ cations [ 29 ], whereas in case of lead the hydrated forms (mainly PbOH + ) also exists besides Pb 2+ ones. Due to the hydration of Pb(II) its diameter increases, which limits their penetration into the adsorbent pores.…”
Section: Resultsmentioning
confidence: 99%
“…It can be the result of different metal species presented in the solution within the acidic range of pH values and their different size. In the solutions of pH lower than 6, the dominant species of copper are Cu 2+ cations [ 29 ], whereas in case of lead the hydrated forms (mainly PbOH + ) also exists besides Pb 2+ ones. Due to the hydration of Pb(II) its diameter increases, which limits their penetration into the adsorbent pores.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorptive decontamination of Cu(II) and Zn(II) from binary solute systems onto carbonaceous materials obtained by chemical activation and ammoxidation of polish brown coal was investigated. 124 The inuence of agitation time, temperature, solution pH, and initial concentration as well as the existence of competing ions on the uptake ability of activated carbons, were studied. It was revealed that the sorption capacity upsurges with increasing concentration and the agitation time and optimum removal were found at pH of 8.00 and 6.00 for Cu(II) and Zn(II), correspondingly.…”
Section: Activated Carbonmentioning
confidence: 99%
“…Thus, it is essential to develop promising techniques for simultaneous removal of Pb(II) and Cd(II) from wastewater prior to their discharge into the environment. To date, the treatment techniques for heavy metals contaminated wastewater mainly include chemical precipitation, electrolysis, ion exchange, biological treatment and adsorption [1][2][3][4][5]. The efficiency of these processes depends on its nature and the contaminated pollutants.…”
Section: Introductionmentioning
confidence: 99%